Field-emission and photo-detection characteristics of laser molecular beam epitaxy grown homoepitaxial GaN nanowall networks. (July 2019) - Tyagi, Prashant; Ramesh, Ch; Sharma, Alka; Husale, Sudhir; Kushvaha, S.S.; Senthil Kumar, M.
Abstract: Field emission and photo-detection properties of homoepitaxial GaN nanowall network structure grown on GaN template by laser molecular beam epitaxy technique are demonstrated. The GaN nanowall network has a tip-width of 8–12 nm and exhibited a band-edge photoluminescence emission at 3.53 eV. From the field-emission characterization, a very low turn-on field of 0.68 V/μm and a high emission current density of 2.22 mA/cm 2 (at 2.38 V/μm) are observed. Photo-detection measurements were also performed on the GaN nanowall network structure under ultraviolet (UV) light irradiation using metal-semiconductor-metal device structure where, a photo-responsivity of 7.28 A/W is obtained at 3 V biasing.